Genetic and functional characterization of Sg-4 glycosyltransferase involved in the formation of sugar chain structure at the C-3 position of soybean saponins. (December 2018) - Takagi, Kyoko; Yano, Ryoichi; Tochigi, Saeko; Fujisawa, Yukiko; Tsuchinaga, Hiroki; Takahashi, Yuya; Takada, Yoshitake; Kaga, Akito; Anai, Toyoaki; Tsukamoto, Chigen; Seki, Hikaru; Muranaka, Toshiya; et al.
Abstract: Triterpenoid saponins are specialized metabolites, which are abundant in soybean seeds. They have a wide variety of effects on human health and physiology. The composition of sugar chain attached to the aglycone moiety of saponins can be controlled by genetic loci, such as Sg-1, 3, and 4 . Among these, the homozygous recessive sg-4 impairs the accumulation of saponins that have an arabinose moiety at the second position of the C-3 sugar chain (i.e., saponins Ad and βa) in the hypocotyls. In this study, we found that sg-4 cultivars are disabled in Glyma.01G046300 expression in hypocotyls. This gene encodes a putative glycosyltransferase (UGT73P10) and is a homolog of GmSGT2 (UGT73P2) whose recombinant protein has been previously shown, in vitro, to conjugate the second galactose moiety at the C-3 position of soyasapogenol B monoglucuronide (SBMG). The sg-4 phenotype (absence of saponins Ad and βa in hypocotyls) was restored by introducing the Glyma.01G046300 genomic DNA fragment that was obtained from the Sg-4 cultivar 'Ibarakimame 7'. Although Glyma.01G046300 is expressed in the cotyledons even in the sg-4 cultivars such as 'Enrei', the induced premature stop codon mutation (W244*) resulted in impaired accumulation of saponin βa in this tissue also in the 'Enrei' genetic background. Furthermore, the recombinant Glyma.01G046300 protein was shown to conjugate the second Ara moiety at the C-3 position of SBMG using UDP-Ara as a sugar donor. These results demonstrate that Sg-4 is responsible for conjugation of the second Ara moiety at the C-3 position of soybean saponins. Graphical abstract: Image 1 Highlights: The sg-4 allele in soybean impairs the accumulation of specific saponins. Evidence that Glyma.01G046300 is responsible for the sg-4 phenotype is provided. Sg-4 ( Glyma.01G046300 ) encodes a UDP-arabinose glycosyltransferase.